"Another Kind of Swede": Swedish Youth's Ethnic Identity Narratives. Issue 1 (February 2018) - Gyberg, Fanny; Frisén, Ann; Syed, Moin; Wängqvist, Maria; Svensson, Ylva
The purpose of this study was to use a narrative approach to investigate the types of ethnicity-related experiences (i.e., ethnic identity content) that were prevalent in the lives of young people in Sweden and to examine if these types of experiences differed due to immigrant status, self-identified ethnicity, or age-groups. Ninety-five participants (87% women, 66% immigrants; 57% emerging adults, 43% adolescents; M age = 19.62) shared their ethnicity-related experiences. Results indicated that youth from immigrant backgrounds more often wrote about ethnicity-related experiences. Thematic analysis revealed six types of stories: feelings of prejudice or racism, general differences, not fitting in, being "another kind of Swede, " being in between cultures or ethnicities, and cultural ideologies. These themes showed little variation by participant immigrant background, ethnicity, or age. The themes found in this study reflect complex and multicultural identities that may play an important part in young people's identity formation.